Teori Kenegaraan Ibnu Khaldun dan Implikasi Etisnya dalam Pemikiran Politik Islam - Fauzan Montanah; Zahira Gefira; Kurniati Kurniati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The Middle Ages in Islamic history is a century filled with thinkers and ideas from various fields. One of the experts at that time was the genius Islamic thinker Ibn Khladun who is famous among modern intellectuals. Ibn Khaldun is considered an expert in the fields of history, sociology, and politics. This research uses a literary method approach to explore the concept of asabiyah in Ibn Khaldun's thought and its implications for the formation and management of the state. Data is collected from various written sources such as books, journals, literature and scientific publications. Ibn Khaldun's view states that asabiyah which contains the spirit of brotherhood and group solidarity can be the key to the success of a country when utilized positively. But if directed negatively to unlimited fanaticism, asabiyah can threaten the stability and justice of government. Ibn Khaldun also underlined the importance of a leader who fulfills the characteristics of Imamah, namely strength, wisdom and the ability to lead fairly in accordance with his religious beliefs. Through understanding the idea of ashabiyah and the principles put forward by Ibn Khaldun, this study highlights the process of forming the state and government by the community. In addition, Ibn Khaldun divided his views on politics into two main components: the state and the leader. He asserted that a state will continue to develop from primitive times to more civilized times, with the expectation of production, civilization, wisdom, and strength that can overcome complex political situations. Therefore, asabiyah is not just an abstract concept, but also has a strong and real influence on the social and political dynamics of society and the people. Ibn Khaldun's work remains an important source of learning in both Western and Eastern countries to this day.